Mitogen-activated protein kinase kinase 1 (MKK1) is negatively regulated by threonine phosphorylation. - Rossomando, A J (1994)
Mitogen-activated protein kinase kinase 1 (MKK1), a dual-specificity tyrosine/threonine protein kinase, has been shown to be phosphorylated and activated by the raf oncogene product as part of the mitogen-activated protein kinase cascade. Here we report the phosphorylation and inactivation of MKK1 by phosphorylation on threonine 286 and threonine 292. MKK1 contains a consensus phosphorylation site for p34cdc2, a serine/threonine protein kinase that regulates the cell division cycle, at Thr-286 and a related site at Thr-292. p34cdc2 catalyzes the in vitro phosphorylation of MKK1 on both of these threonine residues and inactivates MKK1 enzymatic activity. Both sites are phosphorylated in vivo as well. The data presented in this report provide evidence that MKK1 is negatively regulated by threonine phosphorylation.